Bidder Contests in International Mergers and Acquisitions: The Impact of Toeholds, Preemptive Bidding, and Termination Fees - Colin Schneck; Wolfgang Bessler; Jan Zimmermann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We study for a sample of international mergers and acquisitions the effectiveness of three takeover bidding strategies first in preventing bidder contests and second, if a contest has occurred, in increasing the probability of a successful offer. Our results indicate that support for the preemptive bidding hypothesis (signaling with a high cash offer) is limited to bidder contests, where a higher percentage of cash payment increases the likelihood of bidder success. However, evidence that a high initial offer preempts competition is confined to the civil law countries. We find strong evidence for the toehold and termination fee hypotheses, especially after controlling for bidder heterogeneity in bidder contests. Nevertheless, the effect of termination fee provision on deterring competition and on offer success varies across time and countries, while we observe no variation with respect to toeholds. Moreover, we find that latent (but unobservable) competition from financial and foreign buyers is generally not sufficient to curb the influence of actual bidder competition on offer success as well as on target and bidder wealth. We also analyze the impact of acquisition experience and of the expertise offered by reputable financial advisors, and find that serial acquirers are more likely to avoid bidder contests and both, experienced acquirers and bidders employing a reputable advisors, complete a larger proportion of deals. Overall, our results offer new and complementary evidence on the role of strategic bidding in international mergers and acquisitions.
Keywords: D44; G34; G34; 330